A study on factors that influence organizational performance in Kolej Matrikulasi Negeri Sembilan, Negeri Sembilan / Saidatul Athirah Mohd Zafri - Mohd Zafri, Saidatul Athirah (2017)
This research paper involves discussing the factors that influencing organizational performance in Kolej Matrikulasi Negeri Sembilan, Negeri Sembilan. This research has 3 objectives. The goal of this research is to determine the relationship between employee motivation, workplace environment, and training & development towards organizational performance. The scope of this research is focused on the employees in Kolej Matrikulasi Negeri Sembilan in Negeri Sembilan. This has been done by distributing 225 sets of questionnaire to the employees in the organization according to the sample size guide given by Krejcie and Morgan. The survey questionnaire is composed into six parts. Part one about respondent demographic, part two about staff motivation, part three working environment, part four about training and skill and lastly part five about organizational performance. Based on the results from the data that have been collected, there are three findings that has been achieved. The study has shown that there is a positive and weak relationship between employee motivations, workplace environment and training & development with the organizational performance. As a conclusion, all of the research objectives has been achieved. There are a few recommendations that the researcher would like to suggest to the organizational. Firstly, the organization need to play important part in increasing their employees’ motivation. Secondly, the organization must be aware of their working environment because it will affect the organizational performance. Lastly, the organization need to provide enough training for their employees’ so that the employee will have a better understanding and comprehend more about their roles and responsibilities.